2021
DOI: 10.1016/j.molcel.2020.11.046
|View full text |Cite
|
Sign up to set email alerts
|

SALL4 controls cell fate in response to DNA base composition

Abstract: Summary Mammalian genomes contain long domains with distinct average compositions of A/T versus G/C base pairs. In a screen for proteins that might interpret base composition by binding to AT-rich motifs, we identified the stem cell factor SALL4, which contains multiple zinc fingers. Mutation of the domain responsible for AT binding drastically reduced SALL4 genome occupancy and prematurely upregulated genes in proportion to their AT content. Inactivation of this single AT-binding zinc-finger cluste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 90 publications
3
38
0
Order By: Relevance
“…Although Nanog seems relatively density-insensitive during self-renewal, once mESCs are committed to differentiation in -LIF, Nanog protein levels decrease more at LD compared to HD ( Figure 1 I). We also observe more rapid loss of protein expression of pluripotency-related factors Sall4 and Zfp281 ( Luo et al., 2019 ; Pantier et al., 2021 ) at LD. Interestingly, Oct4, Sox2, and Klf5 were downregulated in a density-independent manner, and protein levels of E-cadherin and Zfp57 expression were maintained better in LD compared to HD.…”
Section: Resultsmentioning
confidence: 72%
“…Although Nanog seems relatively density-insensitive during self-renewal, once mESCs are committed to differentiation in -LIF, Nanog protein levels decrease more at LD compared to HD ( Figure 1 I). We also observe more rapid loss of protein expression of pluripotency-related factors Sall4 and Zfp281 ( Luo et al., 2019 ; Pantier et al., 2021 ) at LD. Interestingly, Oct4, Sox2, and Klf5 were downregulated in a density-independent manner, and protein levels of E-cadherin and Zfp57 expression were maintained better in LD compared to HD.…”
Section: Resultsmentioning
confidence: 72%
“…SALL4 was previously shown to interact with the NuRD repressive complex 46 , while interactions with BAF have been largely unexplored. It was recently demonstrated that this transcription factor has an affinity for AT-rich regions 49 , thus providing further support to the ARID1B-SALL4 interaction. SALL4 mutations are also associated with developmental syndromes, including Okihiro syndrome, Holt-Oram syndrome, and Townes-Brocks Syndrome 50 .…”
Section: Resultsmentioning
confidence: 78%
“…SALL4 was previously shown to interact with the NuRD repressive complex 46 , while interactions with BAF have been largely unexplored. It was recently demonstrated that this transcription factor has affinity for ATrich regions 49 , thus providing further support to the ARID1B-SALL4 interaction. SALL4 mutations are also associated with developmental syndromes, including Okihiro syndrome, Holt-Oram syndrome, and Townes-Brocks Syndrome 50 .…”
Section: The Arid1b-baf Complex Exclusively Incorporates Smarca4 As An Atpase Subunitmentioning
confidence: 76%